Aplikasi Damai : Desain Persuasif Aplikasi Konsultasi Kesehatan Mental Berbasis Mobile Menggunakan User Centered Design - Ria Indriyani; Rujianto Eko Saputro; Nia Millatul Izza; Fery Afriansyah; Hasna Salsa Dhia; Samsul Aimah; Irwansyah Munandar; Radeta Tea Makdatuang (Infotekmesin, 2024)
Mental health is health related to a person's emotional, mental and psychological condition. Anxiety disorders are conditions in which individuals experience anxiety for short periods of time or intense episodes, where this anxiety can occur for no apparent reason. Damai is a mobile-based application designed to help overcome mental health problems, especially anxiety disorders among teenagers. This research focuses on designing a user interface that involves users directly at every stage of UCD, starting from user needs, concept design, to implementation of application prototypes. The success of this research was designing a mobile-based mental health consultation application to help teenagers who suffer from mental health. This application successfully provides several features such as mental health tests, online or offline counseling and pharmacy services. In trials conducted on 6 participants, the success of the trial can be concluded that the average direct success was 100%, the misclick rate was 25%, and the average duration was 38.1 seconds.